Lesson Study Through Interactive Groups: The Case of Intercultural Bilingual Education - Pérez Morales, Patricia (2025)
This article analyzes the results of a Lesson Study (LS) focused on mathematics teaching, implemented through Interactive Groups (IG) within learning communities. The analysis is framed as a case study involving 36 preservice teachers and is based on data collected through questionnaires, microcapsules, and portfolios. The information was interpreted to identify the contributions of LS to the training process of preservice teachers (PTs), as well as the role of IGs in organizing collaborative work. The findings highlight how LS enhances PTs’ reflective processes regarding what and how to teach. Furthermore, classroom management through IGs facilitates meaningful interaction and experiential learning among group members.